A case study of air quality - Pesticides and odorous phytochemicals on Kauai, Hawaii, USA. (December 2017) - Wang, Jun; Boesch, Robert; Li, Qing X.
Abstract: This study was conducted after a series of incidences occurred at Waimea Canyon Middle School on Kauai, Hawaii. Some students and staff members exhibited symptoms such as throat irritation, tearing, and dizziness. These symptoms could be associated with natural causes or human activities, which include exposures to pesticides and odorous phytochemicals. At the time of the occurrences, Cleome gynandra (known locally as stinkweed) was growing in the fields near the school and might be a potential cause of the reported symptoms. This work was designed to study pesticides and phytochemicals in ambient air around Waimea Canyon Middle School in comparison with other locations on Kauai. Among many chemicals, top 29 were selected for the analysis of stinkweed-emitted chemicals in a chamber study. One out of the 29 chemicals was methyl isothiocyanate (MITC) that is a highly foul-smelling, noxious chemical at high concentrations. Approximately half of the 29 chemicals produced by stinkweed and trace amounts of five pesticides were detected in indoor and outdoor air samples collected from the passive and high volume air samplers. The average concentrations of MITC in Waimea outdoor air during daytime and nighttime were 13.1 and 5.6 ng m −3, respectively. The average concentrations of the five pesticides DDTs, HCHs, chlorpyrifos, bifenthrin, and metolachlor in Waimea outdoor air were respectively 2.5, 2.3, 35, 43, and 23 ng m −3 during daytime and 2.4, 1.7, 33, 29, and 19 ng m −3 during nighttime. The concentrations of the pesticide and phytochemicals found in air on Kauai were below health concern levels. Graphical abstract: Highlights: This study was prompted by incidences occurred at a school on Kauai, Hawaii. After the incidences, phytochemicals and pesticides were monitored for one year. Five pesticides and many phytochemicals were detected, most at ng m −3 ranges. Methyl isothiocyanate in outdoor air averaged 13.1 ng m −3 daytime.